PDGFRα-positive cell-derived TIMP-1 modulates adaptive immune responses to influenza A viral infection - Dutta, Saugata; Zhu, Yin; Almuntashiri, Sultan; Peh, Hong Yong; Zuñiga, Joaquin; Zhang, Duo; Somanath, Payaningal R.; Ramírez, Gustavo; Irineo-Moreno, Valeria; Jiménez-Juárez, Fabiola; López-Salinas, Karen; Regino, Nora; et al. (American journal of physiology. Lung cellular and molecular physiology, 2025)
Our data strongly link tissue inhibitor of metalloproteinases-1 (TIMP-1) to influenza A virus (IAV) pathogenesis. TIMP-1 is highly increased in PDGFRα-lineage cells during IAV infection. Transforming growth factor-β (TGF-β) induces TIMP-1 during lipofibroblast (lipoFB)-to- myofibroblast (myoFB) transdifferentiation. Timp-1 deficiency protects mice from H1N1 IAV-induced weight loss, mortality, and lung injury. TIMP-1 may be a novel therapeutic target for IAV infection. Tissue inhibitor of metalloproteinases-1 (TIMP-1) is a physiologic inhibitor of the matrix metalloproteinases (MMPs), but little is known about the role of TIMP-1 in regulating the pathogenesis of influenza A virus (IAV) infection. Here, we performed both in vivo and in vitro experiments to investigate the regulation and function of TIMP-1 during IAV infection. Specifically, plasma levels of TIMP-1 are significantly increased in human subjects and wild-type (WT) mice infected with 2009 H1N1 IAV compared with levels in uninfected controls. Also, TIMP-1 is strikingly upregulated in PDGFRα positive (PDGFRα + ) cells in IAV-infected murine lungs as demonstrated using conditional KO (cKO) mice with a specific deletion of Timp-1 in PDGFRα + cells. Our in vitro data indicated that TIMP-1 is induced by transforming growth factor-β (TGF-β) during lipofibroblasts (lipoFBs)-to-myofibroblast (myoFB) transdifferentiation. Timp-1 deficiency protects mice from H1N1 IAV-induced weight loss, mortality, and lung injury. IAV-infected Timp-1-deficient mice showed increased macrophages, and B and T cell counts in bronchoalveolar lavage (BAL) on day 7 postinfection (p.i.), but reduced BAL neutrophil counts. Increased Cxcl12 levels were detected in both BAL cells and lungs from Timp-1-deficient mice on day 3 p.i. Taken together, our data strongly link TIMP-1 to IAV pathogenesis. We identified that PDGFRα-lineage cells are the main cellular source of elevated TIMP-1 during IAV infection. Loss of Timp-1 attenuates IAV-induced mortality and promotes T and B cell recruitment. Thus, TIMP-1 may be a novel therapeutic target for IAV infection. NEW & NOTEWORTHY Our data strongly link tissue inhibitor of metalloproteinases-1 (TIMP-1) to influenza A virus (IAV) pathogenesis. TIMP-1 is highly increased in PDGFRα-lineage cells during IAV infection. Transforming growth factor-β (TGF-β) induces TIMP-1 during lipofibroblast (lipoFB)-to- myofibroblast (myoFB) transdifferentiation. Timp-1 deficiency protects mice from H1N1 IAV-induced weight loss, mortality, and lung injury. TIMP-1 may be a novel therapeutic target for IAV infection.